2022
DOI: 10.36941/jesr-2022-0142
|View full text |Cite
|
Sign up to set email alerts
|

Workplace E-Learning: What, Where, Why and How: A Case Study from the Czech Republic

Abstract: Developments at work and in the workplace are constant activities, and an organisation’s activity in e-learning belongs in this process too. This means that workplace e-learning represents a significant burden for an organisation. A qualitative case study from the Czech Republic was done on the basis of interviews with two groups: content administrators (two respondents) and learners (six respondents), who are familiar with e-learning. Analysis reveals various factors and trends that the organisation must cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Research has demonstrated that the design of digital learning experiences has a significant impact on transfer outcomes in educational and training settings, as technology continues to reshape these environments (Archer, 2021;Bhardwaj, 2019;Wang, 2018). Studies by Beňo et al (2022); Choudhury & Pattnaik (2020) propose that well-organized e-learning modules, virtual reality simulations, and gamified content have the potential to enhance the transfer of knowledge by creating an engaging and interactive training experience.…”
Section: Factors Influencing Transfer Of Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that the design of digital learning experiences has a significant impact on transfer outcomes in educational and training settings, as technology continues to reshape these environments (Archer, 2021;Bhardwaj, 2019;Wang, 2018). Studies by Beňo et al (2022); Choudhury & Pattnaik (2020) propose that well-organized e-learning modules, virtual reality simulations, and gamified content have the potential to enhance the transfer of knowledge by creating an engaging and interactive training experience.…”
Section: Factors Influencing Transfer Of Trainingmentioning
confidence: 99%
“…Employees' motivation to effectively apply their training is enhanced when they perceive support from the organization and observe leaders emphasizing the significance of utilizing newly acquired skills (Amalia, 2020). Research has demonstrated that incorporating e-learning platforms, virtual simulations, and immersive technologies can improve the acquisition of skills by offering authentic and captivating learning experiences (Beňo et al, 2022;Bhardwaj, 2019). The need to enhance individual and organizational effectiveness has arisen due to globalization, technological advancements, and talent development, thus requiring the utilization of training (Choudhury & Pattnaik, 2020;Gallagher et al, 2021;Muduli & Raval, 2018).…”
Section: Transfer Of Training At the Workplacementioning
confidence: 99%